Pendidikan Islam Berbasis Neuroedukasi: Strategi Pembelajaran Al-Qur'an - Khairanis, Retisfa; Aldi, Muhammad (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
Islamic education has an important role in shaping children's character from an early age. However, Qur'anic learning often faces challenges in creating an optimal and enjoyable learning experience. The neuroeducational approach, which integrates the principles of neuroscience in education, offers the potential to improve the effectiveness of Qur'?nic learning. This research aims to explore neuroeducation-based Qur'?nic learning strategies in the context of Islamic education for early childhood. This research used qualitative methods with data collection techniques in the form of in-depth interviews, observation, and document analysis. The research subjects include Islamic education teachers and parents who understand the application of neuroeducation. Data were analyzed thematically to identify effective patterns and strategies in neuroeducational-based Qur'anic learning. The results show that the neuroeducational approach can increase students' motivation to learn, strengthen their understanding of Qur'anic material, and support children's emotional and social development. Teachers who apply this strategy tend to create a learning atmosphere that is interactive, fun, and in accordance with children's brain development. In conclusion, the integration of neuroeducation in Islamic education contributes significantly to improving the quality of Qur'?nic learning. This study recommends training for educators to understand the principles of neuroeducation and its application in Islamic values-based learning. Keyword: Islamic Education, Neuroeducation, Learning Strategy, Al-Qur'an